Sharia Green Economy in Response to Flood Disasters in Sumatra: An Analysis of Maqashid Al-Sharia and Fiqh Bi'ah - Fathiya Nursaldi az-zahrah; Dita Indah Sari Hazuwar; Amirul Hakim (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
This paper examines the role of Maqasid al-Sharia as an ethical and moral framework for developing green economic policies to enhance community and ecosystem resilience to flood disasters in Sumatra. Through literature review and conceptual analysis, this study integrates the principles of Maqashid al-Syariah, particularly hifdz al-din, al-nafs, al-aql, al-nasl, al-mal, and al-bi'ah, with the pillars of green economy, such as resource efficiency, low carbon, and social inclusiveness. It was found that Maqasid al-Shariah provides a robust theological foundation for responsible environmental management and sustainable economic practices, both essential to disaster resilience. This article also identifies Islamic financial instruments, such as Green Sukuk, as a potential financing mechanism for flood-mitigation and adaptation projects. Policy recommendations include strengthening Sharia-based regulations, enhancing environmental education, and strengthening multi-stakeholder collaboration to achieve a more resilient and sustainable Sumatra.